Modification and Testing System Control and Swing Model Excavator System - Suhandi, Anang; Nazaruddin, Nazaruddin (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2015)
One of the heavy equipment that play role in development projects is the excavator. An excavator can perform construction work such as digging, splitting, loading and so on. Laboratory of Hydraulics and Pneumatics Mechanical Engineering Faculty of Engineering, University of Riau has produced a model excavator using pneumatic system, support on a controller box, equipped with buttons setting and motion rotary swing 120°. The research has modifications control system, remove the control box under the excavator and change to the remote system. The motion rotary swing system has changed from 120° to 360°. The purpose is all movements similar in general excavator. The result, excavator model using power 12V DC the control system and compressed air drive pneumatic system. The results of testing control system work to properly, the rotary motion of the swing system 360° and use electric voltage 7,5V will have speed 13,598 rpm, so swing motion from the excavator model similar in general.